Pengaruh Penguasaan Akuntansi Dasar Dan Kosa Kata Bahasa Inggris Terhadap Hasil Belajar Komputer Akuntansi Dengan Motivasi Belajar Sebagai Variabel Moderating - Riska Nurdiyanti; Rochmawati Rochmawati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
This research aimed to prove that there is a significant positive effect between Mastery of Basic Accounting and English Vocabulary on the Learning Outcomes of Computer Accounting. This research also explained that the variable of learning motivation strengthens the effect of Mastery of Basic Accounting and Mastery of English Vocabulary on the Learning Outcomes of Computer Accounting, and also explained that there is a significant positive effect between Learning Motivation on Learning Outcomes of Computer Accounting. This research used a quantitative method. The sample of this research is 61 students of XI grade of Accounting at SMK Negeri 2 Buduran by using the sampling technique of purposive sampling. The method of data collection used in this research is multiple choice tests, questionnaires, and documentation. The test used in this research is test analysis, validity, reliability, classical assumptions, and the MRA test. Based on the result of data analysis, it found that (1) Mastery of Basic Accounting has a significant positive effect on the Learning Outcomes of Computer Accounting (2) Mastery of English Vocabulary has a significant positive effect on the Learning Outcomes of Computer Accounting (3) Learning Motivation strengthens the effect of Mastery of Basic Accounting on the Learning Outcomes of Computer Accounting (4) Learning Motivation strengthens the effect of English Vocabulary on the Learning Outcomes of Computer Accounting (5) Learning Motivation has a significant positive effect on the Learning Outcomes of Computer Accounting